The winter horses - Kerr, Philip (New York : Alfred A. Knopf, 2014)
"Kalinka, a Ukrainian Jewish girl on the run from the Nazis, finds unlikely help from two rare Przewalski horses"--
Keywords: Holocaust, Jewish (1939-1945) -- Ukraine -- Juvenile fiction; Holocaust, Jewish -- Ukraine -- Fiction; Jews -- Ukraine -- Fiction; Przewalski's horse -- Fiction; Horses -- Fiction; Survival -- Fiction; World War, 1939-1945 -- Ukraine -- Fiction; Ukraine -- History -- German occupation, 1941-1944 -- Fiction